2012
DOI: 10.1128/jvi.00571-12
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Nyamanini Virus Replicates in the Nucleus and Exhibits Unusual Genome and Matrix Protein Properties

Abstract: Tick-borne Nyamanini virus (NYMV) is the prototypic member of a recently discovered genus in the order Mononegavirales , designated Nyavirus . The NYMV genome codes for six distinct genes. Sequence similarity and structural properties suggest that genes 1, 5, and 6 encode the nucleoprotein (N), the glycoprotein (G), and the viral polymerase (L), respectively. The function of the other viral genes has been unknown to date. We found that the third NYMV gene codes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Tick-borne Nyamanini virus, a prototypic member of a proposed genus, "Nyavirus," replicates in the nucleus of infected cells like members of the orthomyxoviruses and bornaviruses do (52). Similarly to the N proteins of nucleorhabdoviruses, as stated above, the candidate NLSs in the N protein of Nyamanini and Midway nyaviruses (53) were predicted in our preliminary PSORT analysis (H. Kondo, unpublished result), suggesting that these N proteins also have an important role in the nuclear import of viral RNP (17).…”
Section: Figmentioning
confidence: 99%
“…Tick-borne Nyamanini virus, a prototypic member of a proposed genus, "Nyavirus," replicates in the nucleus of infected cells like members of the orthomyxoviruses and bornaviruses do (52). Similarly to the N proteins of nucleorhabdoviruses, as stated above, the candidate NLSs in the N protein of Nyamanini and Midway nyaviruses (53) were predicted in our preliminary PSORT analysis (H. Kondo, unpublished result), suggesting that these N proteins also have an important role in the nuclear import of viral RNP (17).…”
Section: Figmentioning
confidence: 99%
“…ORF2 was further shown to promote production of infectious virus-like particles by an unknown mechanism (3). Formation of virus-like particles required the simultaneous presence of the viral G protein, the product of ORF4, and the product of ORF2, indicating that ORF2 and ORF4 both play a role in NYMV particle assembly (3). It remains unclear, however, whether ORF4 represents the NYMV-specific equivalent of a matrix protein typically found in negative-strand RNA viruses.…”
mentioning
confidence: 99%
“…The viral nucleoprotein N, the glycoprotein G, and the polymerase L are encoded by ORF1, ORF5, and ORF6, respectively. We recently showed that ORF3 codes for a polymerase cofactor which is required for NYMV polymerase activity (3). The functions of the proteins encoded by ORF2 and ORF4 remain largely unknown.…”
mentioning
confidence: 99%
See 2 more Smart Citations